Mediastinal germ cell tumour causing superior vena cava tumour thrombosis. (25th March 2015) - Karanth, Suman S; Vaid, Ashok K; Batra, Sandeep; Sharma, Devender
Abstract : We report a rare case of a 35-year-old man who presented with a 1-week history of retrosternal chest pain of moderate intensity. A positron emission tomography CT (PET-CT) showed a large fluorodeoxy-glucose (FDG)-avid heterogeneously enhancing necrotic mass in the anterosuperior mediastinum with a focal FDG-avid thrombosis of the superior vena cava (SVC) suggestive of tumour thrombus and vascular invasion. α-Fetoprotein levels were raised (5690 IU/L). Image guided biopsy of the mediastinal mass was suggestive of non-seminomatous germ cell tumour (NSGCT). The patient received four cycles of BEP (bleomycin, etoposide and cisplatin) along with therapeutic anticoagulation with low-molecular-weight heparin. Follow-up whole body PET-CT revealed complete resolution of mediastinal mass and SVC tumour thrombosis. The documentation of FDG-PET-avid tumour thrombus resolving with chemotherapy supports the concept of circulating tumour cells being important not only in common solid tumours such as breast and colon cancer but also in relatively less common tumours such as NSGCT. The detection of circulating tumour cells could help deploy aggressive regimens upfront.